2016
DOI: 10.1016/j.ijmyco.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma cytokines with radiological recovery in pulmonary tuberculosis patients

Abstract: In-depth analysis of cytokines and its association with radiological recovery in TB patients may be useful in monitoring TB patients postchemotherapy for both clinicians and TB control program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Another study suggested CXCR3 ligands (CXCL9 and CXCL10) as useful surrogate markers in plasma for diagnosing active TB clinically (Lee et al, 2015a). More recently, when plasma levels of IL-2, IL-4, IL-6, IL-10, TNF-α, and IFN-γ were determined during the follow-up of anti-TB chemotherapy, slow responders showed significantly higher IL-2 and IL-4 levels at baseline than did fast responders, effectively differentiating the two responder types (Iqbal et al, 2016). Considering these reports, a systematic analysis of immune response genes is essential to understand diverse immune reactions in tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested CXCR3 ligands (CXCL9 and CXCL10) as useful surrogate markers in plasma for diagnosing active TB clinically (Lee et al, 2015a). More recently, when plasma levels of IL-2, IL-4, IL-6, IL-10, TNF-α, and IFN-γ were determined during the follow-up of anti-TB chemotherapy, slow responders showed significantly higher IL-2 and IL-4 levels at baseline than did fast responders, effectively differentiating the two responder types (Iqbal et al, 2016). Considering these reports, a systematic analysis of immune response genes is essential to understand diverse immune reactions in tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cytokines show an unambiguous picture of being either higher or lower in tuberculosis patients' plasma. Particularly, frequently studied candidate cytokines, such as TNF‐α or IFN‐γ, were elevated in the plasma of tuberculosis patients in several studies [20, 23–26, 29, 30, 32, 37, 44, 45, 47, 57, 60, 62, 68–71], but either or both did not differ in other studies [7–10, 14, 15, 18, 20, 21, 23–26, 29–32, 37, 40, 42, 44–47, 51–54, 57, 60–64, 68–71] (Figure 1b). Insufficient study cohort sizes and low statistical power in some studies likely contribute to heterogeneity, but this does not sufficiently explain differences.…”
Section: Heterogeneity Of Plasma Cytokine Expression In Pulmonary Tub...mentioning
confidence: 93%
“…However, to provide an overview of candidates, we screened studies based on a case/control design comparing ‘plasma’ or ‘serum’ samples from patients with pulmonary tuberculosis (before treatment) and matched controls. Sixty studies were identified that meet these criteria [7–66]. The selection criteria used for the definition of ‘controls’ varied between the studies, and this is at least partially due to a missing gold standard for the classification of ‘controls’ in human tuberculosis.…”
Section: Aberrant Plasma Cytokines In Tuberculosis Patients Reflect P...mentioning
confidence: 99%